Merlin/ERM proteins establish cortical asymmetry and centrosome position - Hebert, Alan M. (Cold Spring Harbor Laboratory Press, 2012)
The ability to generate asymmetry at the cell cortex underlies cell polarization and asymmetric cell division. Here we demonstrate a novel role for the tumor suppressor Merlin and closely related ERM proteins (Ezrin, Radixin, and Moesin) in generating cortical asymmetry in the absence of external cues. Our data reveal that Merlin functions to restrict the cortical distribution of the actin regulator Ezrin, which in turn positions the interphase centrosome in single epithelial cells and three-dimensional organotypic cultures. In the absence of Merlin, ectopic cortical Ezrin yields mispositioned centrosomes, misoriented spindles, and aberrant epithelial architecture. Furthermore, in tumor cells with centrosome amplification, the failure to restrict cortical Ezrin abolishes centrosome clustering, yielding multipolar mitoses. These data uncover fundamental roles for Merlin/ERM proteins in spatiotemporally organizing the cell cortex and suggest that Merlin's role in restricting cortical Ezrin may contribute to tumorigenesis by disrupting cell polarity, spindle orientation, and, potentially, genome stability.